Fatty Acids, Amphiregulin Production, and Lung Function in a Cohort of Midwestern Veterans - Corrine Hanson; Jana Ponce; Mia Isaak; Art Heires; Art Heires; Tara Nordgren; Chris Wichman; Jeremy D. Furtado; Tricia LeVan; Tricia LeVan; Debra Romberger; Debra Romberger (Frontiers Media S.A., 2022)
RationaleThe relationship between many fatty acids and respiratory outcomes remains unclear, especially with regard to mechanistic actions. Altered regulation of the process of lung repair is a key feature of chronic lung disease and may impact the potential for pulmonary rehabilitation, but underlying mechanisms of lung repair following injury or inflammation are not well-studied. The epidermal growth factor receptor agonist amphiregulin (AREG) has been demonstrated to promote lung repair following occupational dust exposure in animals. Studies suggest the polyunsaturated fatty acid (PUFA) docosahexaenoic acid (DHA) may enhance the production of AREG. The objective of this study was to determine the relationship between fatty acids and lung function in a population of veterans and determine if fatty acid status is associated with concentrations of AREG.Materials and MethodsData were collected from a cross-sectional study of veterans within the Nebraska-Western Iowa Health Care System. Whole blood assays were performed to quantify AREG concentrations via a commercially available ELISA kit. Fatty acids from plasma samples from the same patients were measured using gas-liquid chromatography. Intakes of fatty acids were quantified with a validated food frequency questionnaire. Linear regression models were used to determine whether plasma fatty acids or intakes of fatty acids predicted lung function or AREG concentrations. A p < 0.05 was considered statistically significant.ResultsNinety participants were included in this analysis. In fully adjusted models, plasma fatty acids were associated with AREG production, including the PUFA eicosapentaenoic acid (EPA) (β = 0.33, p = 0.03) and the monounsaturated fatty acid octadecenoic acid: (β = −0.56, p = 0.02). The omega-3 PUFA docosapentaenoic acid (DPA) was positively associated with lung function (β = 0.28, p = 0.01; β = 26.5, p = 0.05 for FEV1/FVC ratio and FEV1 % predicted, respectively), as were the omega-6 PUFAs eicosadienoic acid (β = 1.13, p < 0.001; β = 91.2, p = 0.005 for FEV1/FVC ratio and FEV1 % predicted, respectively) and docosadienoic acid (β = 0.29, p = 0.01 for FEV1/FVC ratio). Plasma monounsaturated and saturated fatty acids were inversely associated with lung function.ConclusionOpposing anti- and pro-inflammatory properties of different fatty acids may be associated with lung function in this population, in part by regulating AREG induction.